Non-Slave Labour in the Greco-Roman World - Garnsey, Peter (Proceedings of the Cambridge Philological Society Supplementary Volume, 2020)
In Greco-Roman society the typical labourer was a peasant, not a slave. Yet, while specialized studies of ancient slavery abound, the subject of free labour, its incidence, status and economic significance, has received little attention. This volume of essays provides a summary of the available evidence for non-slave labour in antiquity and a bibliographical guide, but in addition advances novel interpretations concerning, for example, the composition of the 'labouring class', the relation between slave and peasant systems of production, and the importance of free dependent labour in the Western Roman provinces.